Modified Daily Undulating Periodization Model Produces Greater Performance Than a Traditional Configuration in Powerlifters. Issue 3 (March 2016) - Zourdos, Michael C.; Jo, Edward; Khamoui, Andy V.; Lee, Sang-Rok; Park, Bong-Sup; Ormsbee, Michael J.; Panton, Lynn B.; Contreras, Robert J.; Kim, Jeong-Su
Abstract : Abstract: Zourdos, MC, Jo, E, Khamoui, AV, Lee, S-R, Park, B-S, Ormsbee, MJ, Panton, LB, Contreras, RJ, and Kim, J-S. Modified daily undulating periodization model produces greater performance than a traditional configuration in powerlifters. J Strength Cond Res 30(3): 784–791, 2016—The primary aim of this study was to compare 2 daily undulating periodization (DUP) models on one-repetition maximum (1RM) strength in the squat, bench press, deadlift, total volume (TV) lifted, and temporal hormone response. Eighteen male, college-aged (21.1 ± 1.9 years) powerlifters participated in this study and were assigned to one of 2 groups: (a) traditional DUP training with a weekly training order: hypertrophy-specific, strength-specific, and power-specific training (HSP, n = 9) or (b) modified DUP training with a weekly training order: hypertrophy-specific, power-specific, and strength-specific training (HPS, n = 9). Both groups trained 3 nonconsecutive days per week for 6 weeks and performed the squat, bench press, and deadlift exercises. During hypertrophy and power sessions, subjects performed a fixed number of sets and repetitions but performed repetitions until failure at a given percentage during strength sessions to compare TV. Testosterone and cortisol were measured at pretesting and posttesting and before each strength-specific day. Hypertrophy, power, and strength produced greater TV in squat and bench press ( p ⩽ 0.05) than HSP, but not for deadlift ( p > 0.05). For squat and deadlift, there was no difference between groups for 1RM ( p > 0.05); however, HPS exhibited greater increases in 1RM bench press than HSP ( p ⩽ 0.05). Effect sizes (ES) showed meaningful differences (ES > 0.50) in favor of HPS for squat and bench press 1RM. Testosterone decreased ( p ⩽ 0.05) at weeks 5 and 6 and cortisol decline at weeks 3 and 4. However, neither hormone was different at posttesting compared with pretesting ( p > 0.05). Our findings suggest that an HPS configuration of DUP has enhanced performance benefits compared with HSP.